The complete mitochondrial genome of the jumping grasshopper Sinopodisma pieli (Orthoptera: Acrididae) and the phylogenetic analysis of Melanoplinae - Liu, Huaxuan; Yan, Liyun; Jiang, Guofang (Zootaxa, 2017)
In this study, we reported the complete mitochondrial genome (mitogenome) of Sinopodisma pieli by polymerase chain reaction method for the first time, the type species of the genus Sinopodisma. Its mitogenome was a circular DNA molecule of 15,625 bp in length, with 76.0% A+T, and contained 13 protein-coding genes, 22 transfer RNA genes and two ribosomal RNA genes and one A+T control region. The overall base composition of the S. pieli mitogenome was 42.8% for A, 33.2% for T, 13.5% for C, and 10.5% for G, respectively. All 13 mitochondrial PCGs shared the start codon ATN. Twelve of the PCGs ended with termination codon TAA and TAG, while cytochrome coxidase subunit 1 (COI) utilized an incomplete T as terminator codon. All tRNA genes could be folded into the typical cloverleaf secondary structure, except trnS(AGN) lacking of dihydrouridine arm. The sizes of the large and small ribosomal RNA genes were 1379 bp and 794 bp, respectively. The A+T rich region was 798 bp in length and contained 88.5% AT content. A phylogenetic analysis based on 13 PCGs by using Bayesian inference (BI) and maximum likelihood (ML) revealed that Sinopodisma is not monophyletic group. We think that the name and taxonomic status of S. tsinlingensis are right, and it should not be moved into the genus Pedopodisma. These data will provide important information for a better understanding of the population genetics and species identification for Sinopodisma.